The Relationship between Chlamydia trachomatis Genital Infection and Spontaneous Abortion - A Ahmadi; M Khodabandehloo; R Ramazanzadeh; F Farhadifar; D Roshani; E Ghaderi; N Farhangi (JRI, 2016)
Background: Chlamydia trachomatis is the etiology of most of sexually transmitted diseases. Colonization of C. trachomatis in the genital tract during early gestation has been associated with preterm birth, and preterm premature rupture of the membranes. The role of C. trachomatis on spontaneous abortion has not yet been proved completely. The aim of this study was to evaluate the frequency of C. trachomatis infection among pregnant women and its association with spontaneous abortion. Methods: This case-control study was conducted from August 2012 until January 2013. Totally, 218 women were included; 109 women with spontaneous abortion with gestation age between 10-20 weeks (cases), and 109 women with normal pregnancy with gestation age between 20-30 weeks (controls) in Sanandaj, Iran. DNA was extracted from endocervical swabs and a PCR test was conducted for detection of C. trachomatis infection in women using specific primers. Independent T-test and Chi-square were used for comparison of quantitative and qualitative variables, respectively, and p<0.05 was considered significant. Results: The total prevalence of C. trachomatis infection was 38(17.43%) in endocervical swabs of women. However, the number of cases with C. trachomatis infections was 25 out of 109(22.9%) in the case group and 13 out of 109(11.9%) in control group, respectively. Association between chlamydia infection and spontaneous abortion was statistically significant (OR=2.198, CI 95%: 1.058-4.56). Conclusion: Our study showed that C. trachomatis infection was associated with spontaneous abortion. Thus, screening and treatment of pregnant women may prevent this adverse pregnancy outcome.